A Relationship Between Self Efficacy And Self Regulation In Diabetes Mellitus Patients - Devi Setya Putri; Alvina Setiani; Luluk Cahyanti (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2025)
Diabetes Mellitus is an incurable disease that affects aspects of life and increases the risk of complications that can cause death. Complications can be minimized if the patient has compliance, knowledge, and ability to perform self-care . The motivation for someone to perform self-care is to have good self-efficacy , while compliance in operate maintenance self influenced by self regulation Where impact on control blood sugar control , diet, and style life . Purpose study for know connection self efficacy with self-regulation in patients with Diabetes Mellitus. The method used quantitative with approach cross sectional . Population in the study This Diabetes Mellitus sufferers at Dr. Loekmono Hadi Kudus Regional Hospital recorded in 2023 were 113 people and determined sample as many as 88 respondents. Results study using the spearman rank test obtained p value of 0.002 (<0.05) which has meaning there is significant relationship​ between self efficacy with self-regulation in patients with Diabetes Mellitus with mark coefficient correlation of 0.332. Conclusion there is connection between self efficacy with self regulation in patients with Diabetes Mellitus.